Biophysical and socio‐economic causes for increasing fallow land in Tamil Nadu. (3rd July 2017) - Dharumarajan, S.; Lalitha, M.; Natarajan, A.; Naidu, L. G. K.; Balasubramanian, R.; Hegde, R.; Vasundhara, R.; Anil Kumar, K. S.; Singh, S. K.
Abstract: The question of increasing fallow land assumes significance at national and international levels due to the decline in net cultivated area and increasing population. Biophysical characteristics of farmland and socio‐economic conditions of farmers are responsible for the increasing fallow. This study was carried out to assess the extent of permanent fallow and identify causes for its increase. High‐resolution remote sensing data were used to identify fallow land in two identified blocks of south India, viz. Nanguneri and Kangeyam. The land resources were characterized, and the specific biophysical and socio‐economic factors responsible for the increasing fallow land were assessed. Multiple regression analysis was carried out to identify the factors responsible for increasing fallows. Soil parameters such as erosion, soil texture, soil depth and available nitrogen contributed significantly ( P > 0.05) to the increase in fallow land. The size of farm holding, number of farm fragments, distance from the road in Nanguneri and farm size and the distance to the nearest town in Kangeyam were socio‐economic factors that had a strong effect ( P > 0.01) on increasing the fallow land. Variable importance rankings in random forest analysis indicated that soil erosion and soil pH had the largest impact on the decision to fallow land in Nanguneri and Kangeyam blocks, respectively. Based on biophysical and socio‐economic constraints, the land resources of fallow land were evaluated for other alternate land use options and policy measures were suggested.